Landscape design of festival marketplace in urban riverfront - 436324 Siti Norwirdaus Abdullah (Skudai : Universiti Teknologi Malaysia, 2007)
Topical Study (Sarjana Muda Senibina Landskap) - Universiti Teknologi Malaysia, 2007